Use of propanolol versus intralesional bleomycin in the management of infantile hemangioma: A comparative study - Ali Raza Chaudhry; Mudassar Fiaz Gondal; Rashid Khan; Inayat Ur Rehman; Rumaisaa Saman; Khawar Abbas (Wolters Kluwer Medknow Publications, 2023)
Background: Infantile haemangiomas (IHs) are widespread vascular tumours having incidence of 10% and most of them involute spontaneously. However, they are known to be located in proximity of vital organs and can have poor cosmetic and functional sequel if left untreated. The aim of the study is to assess the efficacy of oral propranolol and intraleisonal bleomycin in the treatment of infantile cutaneous haemangioma in terms of size regression. Materials and Methods: IH patients presenting in the outpatient department in PIMS were divided randomly by stratified random sampling in two groups. Out of 90 patients, 45 patients had treatment with oral propranolol and other 45 patients received intralesional bleomycin. Baseline size of haemangiomas was taken and regression in size was noted again at 3 and 6 months. Mean and standard deviation were calculated for the age and size of haemangioma in both groups. The mean size regression for both treatments was compared using independent t-test taking P < 0.05 as significant. Results: Out of 90 cases included in this study, the mean age of patients was 10.9 ± 6.1 months in Bleomycin group compared to 10.2 ± 6.9 months in propranolol group. The average size of haemangioma at baseline was 9.5 cm2 in bleomycin group compared to 8.9 cm2 in propranolol group. At 3 months after the intervention, the mean size regression was 3.5 cm2 in bleomycin group compared to 5.3 cm2 in propranolol group and after 6 months of treatment with bleomycin group the mean size of haemangioma was 0.45 cm2, whereas in the propranolol group, it was 2.8 cm2 and difference in the two was found statistically highly significant (P < 0.001). Conclusion: The present study concluded that treatment with intralesional injection Bleomycin for IHs helps in size reduction more efficiently with minimal side effects as compared to oral propranolol for comparable sized haemangiomas.